Nutritional protocols for improving meat quality of feedlot Nellore bulls differing in marbling estimated progeny - Felizari, Luana D. [UNESP]; Squizatti, Mariana M. [UNESP]; Silvestre, Antônio M. [UNESP]; Demartini, Breno L. [UNESP]; Silva, Thaiano I. S. [UNESP]; Souza, Jonata H. R.; Souza, Johnny M. [UNESP]; Pflanzer, Sergio B.; Lanna, Dante P. D.; Johnson, Bradley J.; Toledo, Ariany F. [UNESP]; Millen, Danilo D. [UNESP] (Springer Nature, 2025)
This study aimed to assess the effects of nutritional technologies on marbling precursors in feedlot cattle and their impact on meat quality. One hundred and fifty Nellore bulls with an initial body weight of 403.98 ± 23.82 kg were classified according to their estimated progeny difference (EPD) for marbling and blocked into high or low EPD groups. The bulls were randomly allocated into 30 pens and fed for 112 days in a 2 × 2 + 1 factorial arrangement of treatments: (1) Finely-ground corn (FGC); (2) High-moisture corn (HMC); (3) Finely-ground corn + calcium salts of fatty acids (FGC + CSFA); (4) High-moisture corn + calcium salts of fatty acids (HMC + CSFA); (5) High-moisture corn + calcium salts of fatty acids + organic zinc and chromium (HMC + CSFA + ZnCr). On day 0, one animal per pen (n = 30) was slaughtered to establish baseline meat quality, while the remaining 120 animals were fed until slaughter. Samples of longissimus muscle, 6th to 12th ribs, and its subcutaneous and intramuscular fat were collected for proximate composition, pH, shear force, cooking loss, lipid oxidation, color stability, fatty acid profile, and sensory evaluation. Bulls with high marbling EPD fed HMC + CSFA exhibited greater intramuscular fat (P = 0.03) and cooking loss (P < 0.01), whereas those with low EPD showed higher protein (P < 0.01) and collagen content (P < 0.01). Meat aged for 14 days demonstrated improved tenderness (P < 0.05), although treatments did not influence Warner–Bratzler shear force. Lipid oxidation (P < 0.01) and color variation (ΔE, P < 0.05) increased during retail display with ZnCr supplementation. Fatty acid profiles (SFA, MUFA, PUFA) were significantly affected by EPD × treatment interactions (P < 0.05). Sensory evaluation indicated improved tenderness and overall satisfaction with CSFA supplementation, regardless of corn processing (P < 0.05). In summary, classification by marbling EPD allowed to demonstrate that genetic predisposition interacts with nutritional strategies, highlighting that HMC and CSFA promoted intramuscular fat deposition in high EPD bulls. In contrast, ZnCr supplementation improved oxidative stability and meat color without enhancing marbling.